1979
DOI: 10.1111/j.1432-1033.1979.tb04233.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Newly Synthesized Ribosomal Proteins and Histones in Regenerating Rat Liver with and without Treatment with a Low Dose of Actinomycin D

Abstract: The metabolism of newly synthesized ribosomal proteins in regenerating livers of rats pretreated with a low dose of actinomycin D which selectively inhibits rRNA synthesis, has been. investigated. After 15 min of labeling most newly synthesized proteins were found in the cell sap of regenerating livers of rats pretreated for 1 h with actinomycin D and disappeared from this fraction during a subsequent chase in the presence of cycloheximide. However, no proteinase activity for ribosomal proteins was detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
(4 reference statements)
1
11
0
Order By: Relevance
“…In this paper we describe the presence of a thiol protease in nuclei of regenerating rat liver which may participate in the degradation of newly synthesized ribosomal proteins and histones as reported previously [4]. Partial purification of the enzyme and some properties of it are also reported.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…In this paper we describe the presence of a thiol protease in nuclei of regenerating rat liver which may participate in the degradation of newly synthesized ribosomal proteins and histones as reported previously [4]. Partial purification of the enzyme and some properties of it are also reported.…”
mentioning
confidence: 60%
“…Radioactivity was measured using a toluene-based scintillater containing 30 o/, Triton X-100 as described previously [4] and protein was determined by the method of Lowry et al [16].…”
Section: Determination Of Radioactivity and Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…From the results we have concluded that these two kinds of proteins, which are not associated with the nascent rRNA or DNA, are degraded post-translationally by thiol protease(s) in the nuclei of regenerating rat liver. It must be added that the degradation of newly synthesized and unassociated ribosomal proteins and especially that of histones may occur in the regenerating liver even without actinomycin D treatment [2]. More recently we demonstrated the presence of an acidic protease in the pure nuclei of regenerating rat liver.…”
mentioning
confidence: 88%